(3QSGdI aj eG jJYdb HGdCehGJ aj GdGMJVGQ hZjQgs - (3GdMdj, GdLfGLj, GdfLaj, ef Bd cGTa GdZWGA, LYaQ Hf NVQ Hf TdGd, J (B1227 (3g`s
(3ChdgG (B:s
(3GdMeO ddg Ydi eG CfYe(B...(3bO cKQ Ydj GdEdMGM ef HYV Cgd GdJbhi hGdUdGM Cf CcJH dge QSGdI aj CMcGe GdLfGFR(B...s
(3BNQgG (B:s
(3eHJhQI GdBNQ, hBNQ GdehLhO efgG bhdg(B: ... (3hbO hQO aj GdCNHGQ GdcKjQI Cf GdHcGA Ydi GdejJ dG jSJdRe GdLRY Gdefgj Yfg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B2(3,U(B124s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B491s
(3GdPQjYI(B:(3L(B1(3,U(B295(3,Qbe(B1534s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis